2011
DOI: 10.1371/journal.pone.0028126
|View full text |Cite
|
Sign up to set email alerts
|

Serologic Markers in Relation to Parasite Exposure History Help to Estimate Transmission Dynamics of Plasmodium vivax

Abstract: Plasmodium vivax infection has been gaining attention because of its re-emergence in several parts of the world. Southeastern Turkey is one of the places in which persistent focal malaria caused exclusively by P. vivax parasites occurs. Although control and elimination studies have been underway for many years, no detailed study has been conducted to understand the mechanisms underlying the ineffective control of malaria in this region. Here, for the first time, using serologic markers we try to extract as muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 44 publications
0
29
2
Order By: Relevance
“…A single cross-sectional study investigating the association between anti- Pv SERA4 responses and P. vivax infection showed that both IgG and IgM responders had higher odds of P. vivax detected by light microscopy compared with non-responders (OR = 1.80, 95% CI 0.84 to 3.86, Figure 8 and OR = 2.50, 95% CI 1.39 to 4.49, respectively) [39]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A single cross-sectional study investigating the association between anti- Pv SERA4 responses and P. vivax infection showed that both IgG and IgM responders had higher odds of P. vivax detected by light microscopy compared with non-responders (OR = 1.80, 95% CI 0.84 to 3.86, Figure 8 and OR = 2.50, 95% CI 1.39 to 4.49, respectively) [39]. …”
Section: Resultsmentioning
confidence: 99%
“…This may explain, in part, the differences observed, because in both studies, time of residence in the malaria-endemic area was positively correlated with the anti- Pv MSP-9 response [24,26]. Differential effects according to transmission were also anecdotally observed: one study by Yidez-Zeyrek et al in Turkey [39] showed greater magnitudes of effect with IgM than with IgG responses ( Pv MSP-1 19 and Pv SERA4), indicating that individuals living in this P. vivax -endemic area had limited exposure to P. vivax . Interestingly, the ability of IgG to serve as a marker of exposure in this study was more than twice that of estimates from areas of higher P. vivax transmission (in Brazil and PNG), highlighting the potential for transmission intensity to influence results.…”
Section: Discussionmentioning
confidence: 99%
“…Both IgG1 and IgG3 subclasses are cytophilic, T-cell dependent, and bind strongly to Fcγ, mediating phagocyte activation and complement fixation [ 30 , 31 ], and predominance of IgG1 and/or IgG3, in variable ratios, is common for several P . vivax [ 32 34 ] and P . falciparum merozoite proteins [ 35 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies to PvAMA1 are also associated with P. vivax exposure (Yildiz Zeyrek et al. 2011 ; Fowkes et al. 2012 ), and antibodies to PvAMA1 have been shown to inhibit merozoite invasion in vitro (Vicentin et al.…”
Section: Introductionmentioning
confidence: 99%
“…PvSERA4, which is the most dominantly expressed member of the P. vivax SERA multigene family with an expression profile similar to PfSERA5, has also been shown to stimulate antibody responses (Yildiz Zeyrek et al. 2011 ), but no evidence for functional or protective responses is reported. Antibodies from naturally exposed individuals recognize P. vivax merozoite surface antigens representing polymorphic (PvMSP1 N-terminus, PvMSP3α Block I and II repeats, PvMSP5) and conserved regions (PvMSP1 19 , the extreme N- and C-terminal ends of PvMSP3α and PvMSP10) (Pasay et al.…”
Section: Introductionmentioning
confidence: 99%